Managing the environmental problem of seawater intrusion in coastal aquifers through simulation–optimization modeling. (January 2015) - Singh, Ajay
Highlights: Combined application of simulation–optimization models is necessary. The combined approach can account for the complex pumping optimization problems. The coupling of sharp interface models is easier than the variable density models. The uncertainty analysis and parameter estimation are the major problems. Coupling of socioeconomic aspects in the seawater intrusion modeling is suggested. Abstract: The seawater intrusion is a widespread environmental problem of coastal aquifers where more than two third of the world's population lives. The indiscriminate and unplanned groundwater withdrawal for fulfilling the growing freshwater needs of coastal regions causes this problem. Computer-based models are useful tools for achieving the optimal solution of seawater intrusion management problems. Various simulation and optimization modeling approaches have been used to solve the problems. Optimization approaches have been shown to be of great importance when combined with simulation models. A review on the combined applications of simulation and optimization modeling for the seawater intrusion management of the coastal aquifers are done and is presented in this paper. The reviews revealed that the simulation–optimization modeling approach is very suitable for achieving an optimal solution of seawater intrusion management problems even with a large number of variables. It is recommended that the future research should be directed toward improving the long-term hydraulic assessment by collecting and analyzing widespread spatial data, which can be done by increasing the observation and monitoring networks. The coupling of socioeconomic aspects in the seawater intrusion modeling would be another aspect which could be included in the future studies.